Understanding by design - Wiggins, Grant P., 1950-; McTighe, Jay. (Virginia : ASCD, 2000)
Understanding by design (UbD) guides you through the steps of designing curricular units that promote students' deep content understanding and provide an onerview of the powerful concepts in UbD.Interviews with teachers describe real-world applications of the unit-planning process.
DVD format.
Keywords: Curriculum planning -- United States; Curriculum-based assessment -- United States; Learning; Comprehension